Research of Innovative Activity of Kazakhstan Companies. Example of Tourism and Hospitality Management - DOSZHAN, Raigul; USMANOV, Ali; NURMAGAMBETOVA, Azhar; DAULIYEVA, Galiya; ASSILOVA, Aizhan (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.10.8(40).09, 2020)
In modern conditions, innovative activity is an important component of the process of ensuring the successful performance of an enterprise that actualizes the need for research of this activity. Sociological investigations of economic entities of the innovation system of the Republic of Kazakhstan were conducted in order to identify common problems and conditions of its functioning, as well as to evaluate key factors for the development of innovation business entities and research activities. There have been raised relevant question about the lack of demand for innovation in the country and the question of the imperfection of legislative regulation of innovation activity. Proposals to increase innovation activity, taking into account the scientific research results of other researchers and on the basis of the provisions of the current Kazakhstan legislation are made.